1975
DOI: 10.1042/bj1490387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anions on a monomeric and a dimeric arginine kinase

Abstract: 1. Some effects of anions on the rates of phosphoarginine synthesis by monomeric (lobster) and by dimeric (Holothuria forskali) arginine kinases are reported. 2. As with creatine kinase, acetate ions activate both enzymes: C1-was also found to activate both although this was an inhibitor of creatine kinase. 3. NO3-inhibits the lobster enzyme.Inhibition is of the mixed type with respect to MgATP. K1 >K1' and K, >IK.' indicating that the presence of N03-promotes the binding of substrate and vice versa. 4. NO3-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The activity in the presence of nitrate was only 76% of that with acetate ( Table 1). This is probably explained by the observations of Anosike and Watts ( 1975) that acetate is an activator and nitrate is an inhibitor of lobster muscle arginine kinase. Calcium acetate was only one-fourth as effective as Mg acetate in activating the enzyme (Table 1 ).…”
Section: Resultsmentioning
confidence: 94%
“…The activity in the presence of nitrate was only 76% of that with acetate ( Table 1). This is probably explained by the observations of Anosike and Watts ( 1975) that acetate is an activator and nitrate is an inhibitor of lobster muscle arginine kinase. Calcium acetate was only one-fourth as effective as Mg acetate in activating the enzyme (Table 1 ).…”
Section: Resultsmentioning
confidence: 94%
“…These include the monomer form with a mass of approximately 40 kDa, the homodimer of 80 kDa, and a highly molecular weight form of between 150 and 160 kDa, etc. [17][18][19][20] of AK in energy storage in invertebrates where it is functionally analogous to creatine kinase found in vertebrate, many studies have reported the purification, characterization, properties and unfolding of AK [21][22][23][24]. However, very few authors concentrated on the folding behavior of AK.…”
Section: Introductionmentioning
confidence: 98%
“…4). The planar anion, NO,, inhibits AK by stabilizing the dead-end complex, argi-A B nine-AK-Mg2+-ADP (Anosike and Watts, 1975). In the presence of the ligands, arginine, Mg2+-ADP and NO;, the binding of AK to scallop F-actin was inhibited, as shown by the shift of the binding curve to the right and threefold increase in apparent Kd (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The exaggerated conformational changes that are associated with the stabilization of the abortive arginine -AK-Mg*+-ADP complex by NO; (Anosike and Watts, 1975) might prevent the interaction of AK with actin. Alterations in glycolytic enzyme binding to contractile proteins in the presence of metabolites have been reported (Arnold and Pette, 1970;Yasikowa et al, 1990).…”
Section: + -mentioning
confidence: 99%